2016
DOI: 10.1007/s11069-016-2183-6
|View full text |Cite
|
Sign up to set email alerts
|

FEMA versus local governments: influence and reliance in disaster preparedness

Abstract: This study uses an experimental approach to examine whether disaster information sourced to the Federal Emergency Management Agency (FEMA) influences intentions to adopt hazard adjustments. Survey questions are also used to determine whether individuals rely more on FEMA or local governments when preparing for disasters. Using an online sample of 2008 US employees, the results indicate that information sourced to FEMA is no more influential than information sourced to local governments and that individuals rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…This mirrors results from a previous national survey of U.S. local governments that found places with sustainability goals undertake more community‐oriented economic development actions than those without (Zhang, Warner, and Homsy ). Interestingly, although previous research has found that local governments and volunteers are perceived to be more directly responsibility for resiliency (Sadiq et al ; Singh‐Peterson et al ), our study found that such local motivations played no significant role in disaster planning.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This mirrors results from a previous national survey of U.S. local governments that found places with sustainability goals undertake more community‐oriented economic development actions than those without (Zhang, Warner, and Homsy ). Interestingly, although previous research has found that local governments and volunteers are perceived to be more directly responsibility for resiliency (Sadiq et al ; Singh‐Peterson et al ), our study found that such local motivations played no significant role in disaster planning.…”
Section: Discussioncontrasting
confidence: 95%
“…The social and political capital in rural communities is one key to explaining differences in the level and willingness of communities to act (Flora and Flora ). Trust in resiliency information is higher when it comes from local agencies than from the federal government (Sadiq, Tharp, and Graham ) and, similarly, local volunteer responders are perceived as more prepared for disasters, despite their lack of resources and expertise (Singh‐Peterson et al ).…”
Section: Sustainability Resiliency and Rural Local Governmentsmentioning
confidence: 99%
“…In addition, organization size has the biggest beta coefficient among all the independent variables. This robust finding is in line with the results of myriad studies on hazard adjustments (Quarantelli et al., ; Sadiq, ; Sadiq et al., ). The reason for this result, according to researchers is that larger organizations have more resources than smaller organizations that they can devote to the adoption of hazard adjustments (Dahlhamer et al., ; Mileti et al., ; Tierney, ).…”
Section: Discussionsupporting
confidence: 86%
“…This is because, though the role of FEMA is somewhat limited to the distribution of funding to state and local governments, both FEMA and local governments are the primary authoritative organizations in emergency management. Furthermore, they are the major sources for information regarding emergency preparedness (Basolo et al, 2009;Sadiq et al, 2016).…”
Section: Trust In Issue-specific Agencymentioning
confidence: 99%
“…Although the role of FEMA is somewhat limited to the distribution of funding to state and local governments, both FEMA and local governments are the primary authoritative organizations in emergency management. Furthermore, they are the primary sources of information regarding emergency preparedness (Basolo et al, 2009;Sadiq, Tharp, & Graham, 2016). Therefore, this article claims that, in addition to local government as a major actor in emergency management (Basolo et al, 2009), it is important to investigate individual trust in FEMA and its effect in shaping individuals' levels of emergency preparedness.…”
mentioning
confidence: 99%